Origins of the GATT - British Resistance to American Multilateralism - James N. Miller (Levy Economics Institute of Bard College, 2000)
Fiftieth-anniversary explanations for the efficacy of the GATT imply that the institution's longevity is testimony to the free trade principles upon which it is based. In this light, the predominantly American architects of the system figure as free trade visionaries who benevolently imposed postwar institutions of international cooperation on their war-torn allies. This paper takes issue with such a characterization. Instead, the success of the GATT has been crucially dependent upon its ability to generate pragmatic and detailed policy via a uniquely inclusive forum. An effective institutional procedure, not free trade dogma, has proved key to its endurance–and this feature has been in place since the institution's inception.
Keywords: 330